Nontoxic, Eco‐friendly Fully Water‐Induced Ternary Zr–Gd–O Dielectric for High‐Performance Transistors and Unipolar Inverters. (17th April 2018) - Zhu, Li; He, Gang; Li, Wendong; Yang, Bing; Fortunato, Elvira; Martins, Rodrigo
Abstract: In this context, a simple, nontoxic, and eco‐friendly fully water‐induced (WI) route to fabricate ternary ZrGdO x thin films at various annealing temperatures is reported. Annealing temperature dependent microstructure, morphology, optical, electrical properties, and chemical bonding states of the WI ZrGdO x thin films are investigated by x‐ray diffraction, atomic force microscopy, optical spectroscopy, x‐ray photoelectron spectroscopy, and electrical measurements. A low leakage current density of 10 −8 A cm −2 at 1 mV cm −1 and a large areal capacitance of 531 nF cm −2 at 20 Hz are observed for 400 °C‐annealed ZrGdO x thin films. To verify the possible applications of ZrGdO x thin films as the gate dielectric in thin‐film transistors (TFTs), WI In2 O3 /ZrGdO x TFTs are integrated. 250 °C‐derived full oxide In2 O3 /ZrGdO x TFTs have demonstrated high electrical performance and low operating voltage, including high µ FE of 18.82 cm 2 V −1 S −1, threshold voltage shift of 0.46 V under positive bias stress for 3600 s, and a large I on / I off of 6.01 × 10 7, respectively. Finally, a low voltage resistor‐loaded unipolar inverter is built using In2 O3 /ZrGdO x TFT, exhibiting a linear relationship between supplied voltage and gain voltage and a maximum gain of 7.4 at 2.5 V. These optimized parameters have achieved a low operating voltage of 2 V, which represents a great step toward the achievement of low‐cost, low‐power consumption, and large‐area all‐oxide flexible electronics. Abstract : A simple, nontoxic, and eco‐friendly fully water‐induced route is adopted to fabricate the In2 O3 /ZrGdO x thin‐film transistor and its application in a resistor‐loaded unipolar inverter is investigated. The achieved excellent performance in complementary metal oxide semiconductor logics represents a great step toward the achievement of low‐cost, low‐power consumption, and large‐area all‐oxide flexible electronics.